Ruang Permukiman Tradisional Jawa Berbasis Perlindungan (Preservation of Traditional Javanese Housing) - Santosa, Endratno Budi (Journal of Regional and City Planning, 2016)
Abstract. Traditional Javanese people and society put a lot of philosophy and symbolism in their living practices and daily life. Although in many places this custom is facing great challenges, from historical changes to material developments, there are still people who try to preserve all the traditions inherited from their ancestors. The flexible attitude of the Javanese led to a tradition that emerged as a blend of basic culture and religion (syncretism), which is manifested in a variety of shapes and forms, one of which is the formation of space and the surrounding environment. This paper aims to illustrate as well as compare examples from Javanese spatial culture. There are several basic criteria, including the physical conditions, but the most common is how the spatial organization of a settlement is an attempt or strategy to ask for protection from a higher power, one of which is finding a way to show respect for the ancestors. The studyâs findings show that although the macro-concept is usually the same, the material conditions, the history of a settlementâs formation, and local cultural-religious roots led to the specific forms and spatial patterns of specific settlements.Â Keywords. Traditional settlements, Javanese culture, protection space, ancestor beliefs